Cuarentenas del sur - de Anquín, Ana; Lande, Pablo; Marder, Celia (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
With the title Cuarentenas del sur we take advantage of the current use of the term “cuarentena” to show the existence of the south as a category of exclusion of the global society. Firstly, “cuarentenas” not as an imposed factor for / in the world system which refers to a fragmentation of time and space naturalized as being. And south as cause and effect of not belonging to a society of equal consumers of the market. How are processed in the south the measures that globally oblige to the closure of the housing, at the social distance and at strict hygienic practical distance? We propose to think about the closure to which we are obliged, with, for and pro people and territories we walk: rural communities and urban villas. In this paper we focus on different situations, the villa 21-24 in the neighbourhood of Barracas, in the City of Buenos Aires, less than 5km of the Congress of the Nation and the indigenous communities at the north-east, on the boarders with Bolivia and Chile, at almost 2.000 km from the Federal Capital.